Understanding and enhancing nuclear safety culture in nuclear power plants through a quantitative system dynamics model - Santiago Gregorio Acuña; Marcelo Oscár Gim´enez; Mariela Grinberg; Ochuko Felix Orikpete; Warren Farr (Brazilian Journal of Radiation Sciences)
This study presents a quantitative system dynamics model developed to understand and enhance nuclear safety culture and operational performance in nuclear power plants. The model employs causal loop diagrams and stock-and-flow diagrams, created using Vensim PLE+ software, to capture and simulate the complex interactions that define safety culture dynamics. Recognizing the fundamental role of organizational culture in maintaining nuclear safety, the model incorporates key elements such as leadership, risk perception, continuous improvement, internal communication, and the commitment of management and personnel. Through an extensive literature review and expert consultations, the research integrates critical variables into the model, grounded in frameworks from the International Atomic Energy Agency (IAEA) and the World Association of Nuclear Operators (WANO). Simulating a decade of safety culture management dynamics, the model reveals the impact of management strategies, demonstrating the effectiveness of continuous improvement initiatives and proactive leadership in enhancing safety outcomes. Stress tests conducted under extreme scenarios validated the model's robustness, reaffirming its applicability in safeguarding safety culture under intensified production pressures. The findings provide actionable insights for nuclear safety professionals and decision-makers, promoting environments that support safety-focused practices. This model serves as a comprehensive tool to advance safety culture in nuclear operations, offering valuable perspectives for both theoretical discourse and practical nuclear safety management.